2020
DOI: 10.1002/app.50002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating multi‐step oxidative stabilization behavior of coal tar pitch‐based fiber

Abstract: Oxidative stabilization is an important step for isotropic pitch-based carbon fiber preparation; coal tar pitch-based fiber is treated by multi-step oxidative stabilization under various conditions to investigate the oxidative stabilization mechanism. The chemical structure changes of isotropic pitch-based fiber during the oxidative stabilization and carbonization stage are systematically characterized by In-situ diffuse reflectance infrared Fourier transform, elemental analysis, mass spectroscopy, X-ray photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
(87 reference statements)
0
12
0
Order By: Relevance
“…According to Figure S3, the L-CLRPA/PAN film has a higher O and N content and a lower C and H content than that of the CLRPA/PAN film. The C 1s and O 1s peaks can be devalued into five and four peaks, respectively, as shown in Figure a,b. , The specific peak site and corresponding groups are shown in Table S1. , The L-CLRPA/PAN film shows higher contents of peak 4 (carbonyl group, CO) and peak 5 (carboxyl group, COOH) (Figure d) than the CLRPA/PAN film. Conversely, peaks 1 and 4 of the O 1s exhibit a similar variation tendency (Figure e).…”
Section: Results and Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…According to Figure S3, the L-CLRPA/PAN film has a higher O and N content and a lower C and H content than that of the CLRPA/PAN film. The C 1s and O 1s peaks can be devalued into five and four peaks, respectively, as shown in Figure a,b. , The specific peak site and corresponding groups are shown in Table S1. , The L-CLRPA/PAN film shows higher contents of peak 4 (carbonyl group, CO) and peak 5 (carboxyl group, COOH) (Figure d) than the CLRPA/PAN film. Conversely, peaks 1 and 4 of the O 1s exhibit a similar variation tendency (Figure e).…”
Section: Results and Discussionmentioning
confidence: 97%
“…Yang et al, for example, created a high SP (268 °C) pitch from coal pitch using hydrogenation, polymerization, vacuum, and other processes, resulting in good spinnability . To improve the oxidizing stability of SP pitch-based CFs, optimization of the start temperature, heating rate, or multistep has been employed. ,, Although the aforementioned methods can improve the preparation of low SP pitch-based CF, spinnability is reduced and the cost is greatly increased. Previous research has found that high oxidizing conditions, such as in the presence of iodine, chlorine, or a stronger oxidizing agent, , can accelerate polymerization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fiber-reinforced technique is regarded as an effective method to enhance the mechanical properties of polymers because of the many advantages of fiber materials such as high strength, modulus and stiffness [ 1 , 2 ]. Among various fibers, carbon fiber (CF) with high strength and modulus which can reach 942 MPa and 42.8 GPa, respectively, is considered as the most promising fiber material acting as reinforcement phase [ 3 , 4 ]. The reinforcement effect of CF can be achieved by means of that CF bears the loading transferred from polymer matrix and absorbs partial fracture energy.…”
Section: Introductionmentioning
confidence: 99%